Goat Farming A profitable enterprise in Punjab - Singh, Bharat; Sharma, Ankit; Singh, Gurdeep (Indian Farming, 2016)
Goat farming occupation is becoming a fad with the farmers. Being small-sized animals, farmers found it easy to manage. Feeding, milking and care of goats do not require much equipment and hard work. Four goats can be maintained as cheaply as one indigenous cow. Returns on capital of up to 50% and recovery of 70% of retail price are possible in goat farming. Goats can give more production per unit of investment. Goat meat has no religious taboo and is relished by the non-vegetarian of all sections of society. Goat meat has less fat and is more in demand. In rural areas goat farming can play a vital role in providing gainful employment.